The Cobalt Prince - Siegel, Mark, 1967-; Siegel, Alexis (Siegel, Mark, 1967- 5 worlds, 2018)
Sisters Jessa and Oona, and new friend Ram Sam Sam, try to stop the Cobalt Prince from Toki, who orders a strike on Mon Domani, starting a new war between the worlds.